Achievements and Challenges of Graphene Chemical Vapor Deposition Growth (Adv. Funct. Mater. 42/2022). (18th October 2022) - Liu, Fengning; Li, Pai; An, Hao; Peng, Peng; McLean, Ben; Ding, Feng
Abstract : Chemical Vapor Deposition In article number 2203191, Feng Ding and co‐authors report the vapor‐liquid‐solid growth of graphene nanospears and graphene nanoribbons on Cu surface. The vapor‐liquid‐solid growth of graphene nanostructures is enabled by liquid Si‐Cu catalysts and opens a platform for excellent graphene‐based electronics.